EBV-miR-BART5-5p regulates RORA to promote proliferation and migration of gastric cancer cells - Changqi Du; Shuang Liang; Xia Wang; Yujiao Qi; Shangdong Li; Hongling Li (PLoS ONE, 2025)
Background Epstein-Barr virus-associated gastric cancer (EBVaGC) represents a distinct molecular subtype of gastric cancer. EBV encodes various viral RNAs, including BamHI-A rightward transcripts (BARTs), which are implicated in the carcinogenic processes of EBVaGC. This study aims to explore the function and underlying mechanisms of EBV-miR-BART5-5p in gastric cancer, providing a basis for the identification of more effective biomarkers for EBVaGC. Methods Gene expression data were first downloaded from the GSE51575 dataset to identify differentially expressed genes and construct a WGCNA network, which led to the identification of RORA as a key gene associated with EBV-miR-BART5-5p. We then analyzed the TCGA dataset to investigate the differential expression and prognostic significance of RORA in gastric cancer. Further analysis explored RORA’s enriched pathways and its relationship with immune response, tumor mutation burden, and drug sensitivity. Single-cell gene expression characteristics of RORA were assessed using the GSE134520 dataset. RT-qPCR was employed to determine RORA expression levels in both EBV-positive and -negative gastric cancer cell lines. Western blotting and dual-luciferase reporter assays confirmed the targeting of RORA’s 3’ UTR by EBV-miR-BART5-5p. Finally, a series of functional experiments demonstrated that EBV-miR-BART5-5p promotes proliferation and migration of both EBV-positive and -negative gastric cancer cells. Results In this study, differential expression and WGCNA analyses identified 910 co-expressed genes. We then investigated miR-BART5-5p in EBV-positive gastric cancer and identified RORA as a potential target gene. Our analysis revealed that RORA expression is lower in tumor samples compared to normal samples, and single-cell analysis showed significant upregulation of RORA in CD8 + T cells. Experimental data further demonstrated that RORA is expressed at lower levels in EBV-positive gastric cancer cell lines and that EBV-miR-BART5-5p targets the 3’ UTR of RORA. This suggests that EBV-miR-BART5-5p may promote gastric cancer cell proliferation and migration by regulating RORA. Conclusion Our study reveals the molecular characteristics of EBV-associated gastric cancer, establishes a prognostic model for RORA in gastric cancer, and demonstrates that EBV-miR-BART5-5p may target and inhibit RORA to promote gastric cancer cell proliferation and migration. These findings highlight EBV-miR-BART5-5p could serve as a diagnostic biomarker and a potential therapeutic target for gastric cancer.